Deindustrialization on the Periphery: An Oral History of Sydney Steel, 1945-2001 - MacKinnon, Lachlan (Concordia University, 2016)
This thesis is an historical examination of the multi-layered processes of deindustrialization in Sydney, Nova Scotia. The history of a steel plant formerly located in the centre of the city is used as a case study through which the mechanisms of deindustrialization are fully explored. In 1967, the provincial government of Nova Scotia nationalized the Sydney Works. This marks a significant divergence from previous studies of deindustrialization, which have traditionally focused on the wave of industrial closures in the North American heartland during the 1970s and 1980s. Framed by oral history accounts of former steelworkers, this dissertation reveals the combined impact of Canadian regionalism, political economy, and working-class cultures of resistance on local experiences of industrial decline. This represents a synthesis between the econo-political historiography of deindustrialization favoured in the 1980s and the cultural/representational approaches of the 1990s and 2000s. The title, “Deindustrialization on the Periphery,” speaks to the specific national and regional contexts that frame the decline of Sydney Steel. The longue durée of economic change on the rural resource frontier has been understudied. In Cape Breton, the devastation wrought by the end of industry has roots that stretch back to the early 20th century. Tracing these through the use of Harold Innis’ “staples trap,” my thesis reveals how deindustrialization stretches from decades before closure to the years after a mine, mill, or factory are shuttered for the last time. Workers and other residents in Sydney continue to face the bodily aftermath of workplace injury, occupational, and environmental illness long after the structures of the plant have been demolished. But so, too, have experiences of working at the mill and living in the neighbourhoods that surrounded its gates created particular forms of culture, solidarity, and identity. My research is more than a eulogy for a defunct steel town. It seeks to expose the tensions between different forms of memory and experience, and to examine how the industrial past remains inextricably connected to the “post-industrial” present.
https://cha-shc.ca/prize-winner/lachlan-mackinnon/